Unusually Devastating Tornadoes in the United States: 1995–2016. Issue 3 (3rd May 2020) - Fricker, Tyler; Elsner, James B.
Abstract : Previous research has identified a number of physical, socioeconomic, and demographic factors related to tornado casualty rates. There remain gaps in our understanding of community-level vulnerabilities to tornadoes. Here a framework is provided for systematically identifying the most unusually devastating tornadoes, defined as those where the observed number of casualties far exceeds the predicted number. Results show that unusually devastating tornadoes occur anywhere tornadoes occur in the United States, but rural areas across the Southeast appear to be most frequented. Seven examples of unusually devastating tornadoes affecting six communities are examined in more detail. In addition, results highlight that cities and towns affected by unusually devastating tornadoes have their own socioeconomic and demographic profiles. Identifying geographic clusters of unusually devastating tornadoes builds a foundation to address community-level causes of destruction that supports ethnographic and qualitative—in addition to quantitative—studies of place-based vulnerability. Key Words: statistics, tornado, vulnerability.